Detection of ureaplasma urealyticum by polymerase chain reaction examination in nonspecific genital infection patients - R. Rahmadewi; Dian PH (PAGEPress Publications, 2019)
Non specific genital infection (NSGI) is a condition affecting females which causes inflammation of the endocervix or anterior urethra that is not caused by Neisseria gonorrhoeae. The causative sexually transmitted organisms include Chlamydia trachomatis (Groups D to K) and Ureaplasma urealyticum. Infection caused by Ureaplasma urealyticum is often asymptomatic even though many studies have pronounced that Ureaplasma urealyticum can contribute not only to lower genitourinary infection but also to infertility. Ureaplasma urealyticum cannot be stained by Gram stain due to the lack of a cell wall of the organism. This research aims to evaluate the prevalence of Ureaplasma urealyticum in NSGI patients by using the polymerase chain reaction (PCR) method targeted in the ureaplasma gene structure 429 bp area. The samples were extracted from eighteen DNA NSGI patients. Eleven out of eighteen (61.11%) DNA NSGI samples tested positive for Ureaplasma urealyticum. Most patients (44.44%) with Ureaplasma urealyticum were unemployed, and 27.78% were complaining of recurrent vaginal discharge. The high incidence of Ureaplasma urealyticum in this study needs further attention since doxycycline remains the drug of choice of NSGI. Moxifloxacin should be considered for patients who are making no clinical progress with doxycycline.